Astragalus–Scorpion Drug Pair Inhibits the Development of Prostate Cancer by Regulating GDPD4-2/PI3K/AKT/mTOR Pathway and Autophagy - You, Xujun; Wu, Yongrong; Li, Qixin; Sheng, Wen; Zhou, Qing; Fu, Wei (Frontiers in Pharmacology, 2022)
Objective: Prostate cancer (PCa) is an epithelial malignancy of the prostate that currently lacks effective treatment. Traditional Chinese medicine can play an anticancer role through regulating immune system, anti-tumor angiogenesis, regulating tumor cell apoptosis, autophagy dysfunction and other mechanisms. This study attempted to explore the active ingredients and potential mechanism of action of Astragalus-Scorpio (A-S) drug pair in PCa, in order to provide new insights for the treatment of PCa. Methods: Network pharmacology was used to analyze of A-S drug pair and PCa targets. Bioinformatics analysis was used to analyze the LncRNAs with significant differences in PCa. The expression of LC3 protein was detected by immunofluorescence. CCK8 was used to detect cell proliferation. The expressions of GDPD4-2, AC144450.1, LINC01513, AC004009.2, AL096869.1, AP005210.1 and BX119924.1 were detected by RT-qPCR. The expression of PI3K/AKT/mTOR pathway and autophagy related proteins were detected by western blot. LC-MS/MS was used to identify the active components of astragalus and scorpio. Results: A-S drug pair and PCa have a total of 163 targets, which were mainly related to the Prostate cancer and PI3K/AKT pathways. A-S drug pair inhibited the formation of PCa, promoted the expression of LC3Ⅱ and Beclin1 protein, and inhibited the expression of P62 and PI3K-AKT pathway proteins in PCa mice. Astragaloside IV and Polypeptide extract from Scorpion venom (PESV) were identified as the main active components of A-S drug pair. GDPD4-2 was involved in the treatment of PCa by Astragaloside IV-PESV. Silencing GDPD4-2 reversed the therapeutic effects of Astragaloside IV-PESV by regulating the PI3K/AKT/mTOR pathway. Conclusion: Astragaloside IV-PESV as the main active components of A-S drug pair treated PCa by regulating the GDPD4-2/PI3K-AKT/mTOR pathway and autophagy.